Utilization of Cold Lava Material from Mount Marapi Volcano as Road Embankment in West Sumatra, Indonesia - Yory Yananza; andriani andriani; Muhammad Shubhi Nurul Hadie; Afra Inayah Putri (Teras Jurnal : Jurnal Teknik Sipil, 2026)
Abstrak   Gunung Marapi merupakan salah satu gunung api aktif di Sumatra Barat yang sering mengalami erupsi. Material hasil erupsi seperti abu vulkanik, pasir, dan batuan piroklastik tersebar di sekitar kawasan terdampak, termasuk di daerah Bukit Batabuah, Kabupaten Agam. Pemanfaatan material ini sebagai bahan konstruksi, khususnya untuk timbunan jalan, menjadi opsi menarik untuk mendukung pembangunan infrastruktur berkelanjutan. Penelitian ini bertujuan untuk mengidentifikasi kesesuaian material lahar dingin sebagai bahan timbunan jalan.  Hasil pengujian menunjukkan bahwa material lahar dingin Gunung Marapi berupa tanah pasir dengan gradasi baik, nilai California Bearing Ratio (CBR) > 6 % dan tidak terjadi pengembangan selama proses perendaman; sudut geser dalam (φ)  > 30o dan kohesi (c) antara 0.005 kg/cm2 – 0.037 kg/cm2. Berdasarkan Surat Edaran Dirjen Bina Marga No. 16.1/ SE/ Db/ 2020 tentang Spesifikasi Umum 2018 untuk pekerjaan konstruksi jembatan dan jalan, maka material ini  cocok digunakan sebagai material timbunan pilihan.   Kata kunci: Lahar dingin; Gunung Marapi; timbunan jalan; California Bearing Ratio (CBR); kekuatan geser   Abstract Mount Marapi is one of the active volcanoes in West Sumatra that frequently erupts. Eruption materials such as volcanic ash, sand, and pyroclastic rocks are scattered around the affected areas, including in the Bukit Batabuah area, Agam Regency. Utilizing these materials as construction materials, especially for road embankments, is an attractive option to support sustainable infrastructure development. This study aims to identify the suitability of cold lava material as road embankment material. The test results show that the cold lava material of Mount Marapi is sandy soil with good gradation, a California Bearing Ratio (CBR) value of > 6% and no swelling during soaked process; an internal friction angle (φ) of > 30o and cohesion (c) between 0.005 kg/cm2 – 0.037 kg/cm2. Based on the Circular Letter of the Director General of Highways No. 16.1/ SE/ Db/ 2020 concerning General Specifications 2018 for bridge and road construction work, this material is suitable for use as the selected embankment material.   Keywords: cold lava; Mount Marapi; road embankment; California Bearing Ratio (CBR); shear strength